CMOS optical centroid processor for an integrated Shack-Hartmann wavefront sensor - Pui, Boon Hean (2004)
A Shack Hartmann wavefront sensor is used to detect the distortion of light in an optical wavefront. It does this by sampling the wavefront with an array of lenslets and measuring the displacement of focused spots from reference positions. These displacements are linearly related to the local wavefront tilts from which the entire wavefront can be reconstructed. In most Shack Hartmann wavefront sensors, a CCD is used to sample the entire wavefront, typically at a rate of 25 to 60 Hz, and a whole frame of light spots is read out before their positions are processed. This results in a data bottleneck. In this design, parallel processing is achieved by incorporating local centroid processing for each focused spot, thereby requiring only reduced bandwidth data to be transferred off-chip at a high rate. To incorporate centroid processing at the sensor level requires high levels of circuit integration not possible with a CCD technology. Instead a standard 0.7J..lmCMOS technology was used but photodetector structures for this technology are not well characterised. As such characterisation of several common photodiode structures was carried out which showed good responsitivity of the order of 0.3 AIW. Prior to fabrication on-chip, a hardware emulation system using a reprogrammable FPGA was built which implemented the centroiding algorithm successfully. Subsequently, the design was implemented as a single-chip CMOS solution. The fabricated optical centroid processor successfully computed and transmitted the centroids at a rate of more than 2.4 kHz, which when integrated as an array of tilt sensors will allow a data rate that is independent of the number of tilt sensors' employed. Besides removing the data bottleneck present in current systems, the design also offers advantages in terms of power consumption, system size and cost. The design was also shown to be extremely scalable to a complete low cost real time adaptive optics system.